Effect of Gender on Academic Competence of Primary Education Department Students of College of Education Akwanga Nasarawa State Nigeria - Odagboyi, Isaiah Amedu (Advances in Social Sciences Research Journal, 2015)
This study was undertaken to find out if there is any significant difference in the performance of males and females in the Primary Education Department of the College of Education. Akwanga. The sample for the study was made up of a set of students admitted into the department in the 2011/2012 academic session. There were 127 males, and 74 females, making a total of 201 students. One null hypothesis was formulated to guide the study. Session results of the students that have been summarized into Grade Point Average (GPA),were obtained from the department and separated according to gender. The data so obtained were subjected to the t-test at 0.05 level of significance. Results showed that there was no significant difference between the performance of the males and the females. It was suggested that more research be conducted to find out the influence of culture on gender as it affects achievement of students in schools, taking note of such differences at the various levels of education from primary to tertiary levels.